Enhancing the Tolerance of a Green Foxtail Biotype to Mesotrione via a Cytochrome P450-Mediated Herbicide Metabolism - Yuning Lan; Yi Cao; Ying Sun; Ruolin Wang; Zhaofeng Huang (Agronomy)
Green foxtail is a troublesome weed in crop fields across China. A nova target HPPD inhibitor is widely used to control weeds in agricultural production. Mesotrione, an HPPD inhibitor, cannot control green foxtail effectively under the recommended field dose, indicating that green foxtail is tolerant to mesotrione. Interestingly, a green foxtail biotype that exhibits a greater tolerance to mesotrione (GR50 value 463.2 g ai ha−1) than that of the wild biotype (GR50 value 271.9 g ai ha−1) was found in Jilin Province, China. The HPPD genes isolated from the two biotypes genome were aligned, while no difference was found in the amino acid of the HPPD compared with that of the wild biotype. Through the qPCR experiment, the HPPD gene copy number variation and overexpression were also not found. Cytochrome P450 inhibitors (malathion and PBO), pretreatment, could effectively reverse the tolerance. Compared with the MT biotype, the in vivo activity of P450s was higher after the mesotrione treatment in the HT biotype. Therefore, P450s might be involved in the mechanism of tolerance.